Full‐text publication rates of research abstracts presented at the European Society of Endodontology congresses in the last 20 years. (15th July 2017) - Tzanetakis, G. N.; Tzimpoulas, N.; Floratos, S.; Agrafioti, A.; Kontakiotis, E. G.; Shemesh, H.
Abstract: Aim: To evaluate the full‐text publication rates of scientific research abstracts presented at the European Society of Endodontology (ESE) congresses held between 1993 and 2013 (a total of 11 occasions) and to determine factors associated with the manuscripts. Methodology: An electronic database search was conducted from January 2015 to December 2016 to identify full‐text English‐written publications of the research abstracts presented at the last 11 ESE Biennial congresses from 1993 to 2013. For each occasion, research abstract information was retrieved from the International Endodontic Journal (IEJ) through the official website of the ESE, and the following parameters for each abstract presentation were recorded: year of presentation, first author's affiliation, geographic origin and type of study. Following full‐text article identification, additional information was recorded such as: year and journal of publication, elapsed time until full publication and number of authors per presentation and publication. Results: A total of 1165 research abstracts were presented, of which 401 (34.4%) were finally published as full‐length articles. Overall 235 articles (58.6%) were published either in the International Endodontic Journal (IEJ, 35.7%) or Journal of Endodontics (JOE, 22.9%). The mean time between abstract presentation and full‐text publication was 18.95 months. Munich (2001) had the highest publication rate (44%), whereas Lisbon (2013) had the highest number of published articles (77). Turkey was the country with the highest number of published abstracts (56). However, the Netherlands was the country with the highest number of publications related to the number of presentations (21/26) (80.7%). Differences in authorship between presentation and full publication were found in 179 (44.6%) articles. Conclusion: A substantial number of research abstracts presented at ESE congresses were not published in peer‐reviewed journals. Authors prefer to publish their research papers in international journals with high impact factor.